Agama dan Postmodernisme: Menelusuri Metodologi dan Pendekatan Studi-Studi Agama - Syafwan Rozi (ILMU USHULUDDIN, 2012)
Postmodernism is a critical reflection on the paradigms of modernism and the era of the rise of religious spirituality. In this respect, the emergence of social theory in the perspective of postmodernism makes the approach and methodology of religious studies growing richer. Among these are the Foucauldian approach, Derrida’s and Habermas’ concepts. Apart from that, discourse of Foucauldian dealing with archaeological- genealogical perspective in complementary can form a critical perspective for religious studies, and socially unveil the workings of a regional and practical power relation. In addition, the perspective of deconstruction by Derrida offers not only a way to read a text, but also social reality, to undermine the status of a dominant and repressive discourse and other social practices. In fact, Habermas’ critical theory in the style of criticism is against the methodology creating ‘religious’ discourse which is impartial and oppressive.